2001
DOI: 10.4319/lo.2001.46.8.1956
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of natural colloid‐bound iron to marine plankton: Influences of colloidal size and aging

Abstract: Iron (Fe) is mostly complexed with the organic ligands or colloids that are very abundant in natural seawater. In this study, natural colloids were isolated by ultrafiltration and radiolabeled with 59 Fe. The biological uptake of radiolabeled colloid-bound Fe of different sizes (1-10 kDa and 10 kDa-0.2 m) and ages (1 and 15 d) by diatoms (Thalassiosira pseudonana) and copepods (Acartia spinicauda) was then determined. The uptake of radiolabeled colloid-bound Fe was compared with the uptake of low molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 52 publications
3
64
2
Order By: Relevance
“…Experimental work suggests that iron-bearing colloids harvested from seawater are only partially bioavailable to eukaryotic organisms. Chen and Wang (2001) carried out experimental studies of diatom growth in seawater spiked with colloids/nanoparticles harvested from seawater and separated into two size fractions (approximately <5 nm and 5 nm to 0.2 µm), each labelled with 56 Fe. Uptake of iron from the smaller size fraction exceeded that from the larger, but both fractions were used less readily than Fe present as low molecular weight aqueous complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work suggests that iron-bearing colloids harvested from seawater are only partially bioavailable to eukaryotic organisms. Chen and Wang (2001) carried out experimental studies of diatom growth in seawater spiked with colloids/nanoparticles harvested from seawater and separated into two size fractions (approximately <5 nm and 5 nm to 0.2 µm), each labelled with 56 Fe. Uptake of iron from the smaller size fraction exceeded that from the larger, but both fractions were used less readily than Fe present as low molecular weight aqueous complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Both forms of iron are assumed to be equally susceptible to consumption by phytoplankton despite recent observations suggest that this may be not the case (Nishioka and Takeda, 2000;Chen and Wang, 2001;Chen et al, 2003). In other words, the total bioavailable concentration of iron is equal to the total dissolved iron concentration (Fe).…”
Section: Simple Chemistry Modelmentioning
confidence: 99%
“…The major proportion of the dissolved Fe in open ocean seawater (here defined as 0.4 µm filtered) was found to be in the colloidal form (here defined as >0.02 µm-0.4 µm) (Wu et al, 2001), with continuing debate about the bioavailability of this fraction. Chen and Wang (2001) showed that freshly precipitated colloids were available to phytoplankton but aging processes (15 days) reduced markedly their availability. Wang and Dei (2003) demonstrated that Fe availability from colloidal matter to cyanobacteria (Synechococcus, Trichodesmium) is largely dependent on the size and origin of the material, with the tendency of Fe bound to smaller colloids and biogenic colloidal material derived from the same species being more available.…”
Section: Colloidal Iron and Organic Mattermentioning
confidence: 99%